Factors affecting the impact of professional development programs on teachers' knowledge, practice, student outcomes & efficacy. - Ingvarson, Lawrence; Meiers, Marion; Beavis, Adrian (Education Policy Analysis Archives, 2005)
This report examines effects of structural and process features of professional development programs on teachers' knowledge, practice and efficacy. It is based on four recent (2002-2003) studies undertaken through the Australian Government Quality Teacher Programme, designed to enhance teacher quality. The total data set for the survey study includes 3,250 teachers who had participated in eighty individual professional development1 activities within these studies. Teachers were surveyed at least three months after participating in an activity, which provided them with the opportunity to gauge the impact of programs on their practice. To investigate factors affecting impact, a theoretical model was developed based on recent research into the characteristics of effective professional development and tested using blockwise regression analysis. The model included contextual factors (e.g., school support), structural features of programs (e.g. ,length), process features (e.g., emphasis on content; active learning; examination of student work; feedback; follow-up), a mediating variable (level of professional community generated), and four outcome measures (knowledge; practice; student learning and efficacy). Consistent significant direct effects were found across the four studies for the impact of content focus, active learning, and follow-up on knowledge and professional community. Feedback was rarely incorporated into program design. Impact on efficacy was strongly related to the perceived impact of activities on teachers' practice and student learning outcomes.